Character association and path analysis of morphological and economic traits in cabbage (Brassica oleracea var. capitata - SINGH, B K; SHARMA, S R; KALIA, P; SINGH, B (The Indian Journal of Agricultural Sciences, 2011)
The character association and path co-efficient analysis was carried out during 2005–07 after field evaluation of 36 genetically diverse exotic and indigenous genotypes of cabbage (Brassica oleracea L. capitata L.). The positive association between days to 50% maturity and number of non-wrapper leaves suggested the selection of plants having less number of non-wrapper leaves so as to evolve early-maturing genotypes. Negative association of head compactness with polar diameter, equatorial diameter, frame spread, plant height, gross plant weight and core length, on the other hand, implied to select plants with smaller measurements for the latter morphological and economic traits which will not only help in improved compactness of head but also in marketability, shelf-life and consumers’ preference. Gross plant weight proved to be the most effective direct selection index for genetic improvement of cabbage.